Doctrinal adaptation of green instruments and their issuance controls - Al-Saadi, Mohammed Omar; Al-Hababsa, Hamza Hussein Qutaish (Journal of Islamic Sciences, 2022)
This study dealt with the jurisprudential adaptation of green sukuk and the controls for their issuance, and green sukuk is a new Islamic financial tool that is interested in investing in environmentally friendly and socially responsible projects. the inductive study; By following the phenomenon under study to reveal its truth and legitimacy, the comparative approach by comparing the green bonds and the green bonds, the analytical approach in order to root, adapt, elicit the legal ruling and achieve the partial and total terms. The study continued to the most important results, including: that green sukuk are securities that comply with the provisions of Islamic Sharia, and are directed towards green investments and environmentally friendly projects that are socially responsible within the framework of sustainable development, and that the doctrinal adaptation of green sukuk is that they belong to the provisions of participation and fall under the same concept, participation depends on investment. By mixing funds, with the aim of profit and participation, and increasing the profits of the few financial contributions, the study recommends the need to spread awareness about the importance of green Islamic sukuk, and what it can offer from the collection of capital in accordance with the principles of Islamic Sharia, directed towards sustainable environment projects with providing incentives and encouraging investment. In which.